First- and second-generation integrated process for bioethanol production: Fermentation of molasses diluted with hemicellulose hydrolysate by recombinant Saccharomyces cerevisiae - de Oliveira Pereira, Isabela; dos Santos, Ângela A.; Guimarães, Nick C.; Lima, Cleilton S.; Zanella, Eduardo; Matsushika, Akinori; Rabelo, Sarita C. [UNESP]; Stambuk, Boris U.; Ienczak, Jaciane L. (Wiley, 2024)
The integration of first- (1G) and second-generation (2G) ethanol production by adding sugarcane juice or molasses to lignocellulosic hydrolysates offers the possibility to overcome the problem of inhibitors (acetic acid, furfural, hydroxymethylfurfural and phenolic compounds), and add nutrients (such as salts, sugars and nitrogen sources) to the fermentation medium, allowing the production of higher ethanol titers. In this work, an 1G2G production process was developed with hemicellulosic hydrolysate (HH) from a diluted sulfuric acid pretreatment of sugarcane bagasse and sugarcane molasses. The industrial Saccharomyces cerevisiae CAT-1 was genetically modified for xylose consumption and used for co-fermentation of sucrose, fructose, glucose, and xylose. The fed-batch fermentation with high cell density that mimics an industrial fermentation was performed at bench scale fermenter, achieved high volumetric ethanol productivity of 1.59 g L−1 h−1, 0.39 g g−1 of ethanol yield, and 44.5 g L−1 ethanol titer, and shown that the yeast was able to consume all the sugars present in must simultaneously. With the results, it was possible to establish a mass balance for the global process: from pretreatment to the co-fermentation of molasses and HH, and it was possible to establish an effective integrated process (1G2G) with sugarcane molasses and HH co-fermentation employing a recombinant yeast.
Keywords: co-fermentation; hemicellulosic hydrolysate; molasses; propagation; recombinant yeast